Collaborative leadership : its manifestation in Vietnam - Dang, Linh (2020)
The constantly changing world that we live today affects several aspects of life, and education is no exception. Therefore, the call for more collective actions is increasing as a positive way to cope with the uncertain environment. Out of several approaches to collaboration, collaborative leadership is proved to be highly effective. The purpose of this study is to uncover the manifestation of collaborative leadership as a novel theoretical model and collaborativeness as a process in Vietnam setting. Due to the contextual differences between the West (where the approach is established) and the East (where the study is conduct-ed), the author expects to identify differences and similarities in the way collaborative leadership is manifested. Therefore, Schein’s culture level model is used as a cultural lens to decipher participants’ thoughts and opinions.